Plant growth-promoting rhizobacteria enhance salinity stress tolerance in okra through ROS-scavenging enzymes - Habib, Sheikh Hasna; Kausar, Hossain; Mohd Saud, Halimi (Hindawi Publishing Corporation, 2016)
Salinity is a major environmental stress that limits crop production worldwide. In this study, we characterized plant growth-promoting rhizobacteria (PGPR) containing 1-aminocyclopropane-1-carboxylate (ACC) deaminase and examined their effect on salinity stress tolerance in okra through the induction of ROS-scavenging enzyme activity. PGPR inoculated okra plants exhibited higher germination percentage, growth parameters, and chlorophyll content than control plants. Increased antioxidant enzyme activities (SOD, APX, and CAT) and upregulation of ROS pathway genes (CAT, APX, GR, and DHAR) were observed in PGPR inoculated okra plants under salinity stress. With some exceptions, inoculation with Enterobacter sp. UPMR18 had a significant influence on all tested parameters under salt stress, as compared to other treatments. Thus, the ACC deaminase-containing PGPR isolate Enterobacter sp. UPMR18 could be an effective bioresource for enhancing salt tolerance and growth of okra plants under salinity stress.